Career intervention effectiveness and motivation: blended and distance modalities comparison - Monteiro, Sílvia; Seabra, Filipa; Santos, Sandra; Almeida, Leandro S.; Almeida, Ana Maria Tomás de (Revista de estudios e investigación en psicología y educación, 2025)
This study evaluates the effectiveness of an intervention program on career resources in the blended and distance modalities and explores the relationship between changes in career resources and self-determined motivation. For this purpose, two groups of 68 and 72 higher education students participated in blended and distance career interventions, respectively. The blended program took place in a curricular infusion context, and was subject to assessment, while the distance program was fully voluntary. Students were assessed with pre- and post-tests regarding four career resources’ dimensions. Motivation over program experience was assessed after the intervention. The results indicate that despite some differences between the two modalities, both career interventions were effective, with gains in three of the four assessed career resources’ dimensions. Relatedness was higher in the blended format of the program, while participants in the distance format reported experiencing higher levels of autonomy during the program. Despite that, motivation variables did not present a relevant predictive power in career resources’ gains obtained through participation in the program. Implications for practice include the possibility of infusing the program into curricula of higher education degrees as a way of increasing program completion and reaching different audiences and highlighting the importance of using multiple approaches to broaden its reach. O presente estudo avalia a eficácia de um programa de intervenção nos recursos de carreira nas modalidades blended e a distância, e explora a relação entre as mudanças nos recursos de carreira e a motivação autodeterminada. Para tal, dois grupos de 68 e 72 estudantes do Ensino superior participaram em intervenções blended e a distância, respetivamente. O programa blended teve lugar num contexto de infusão curricular e foi sujeito a avaliação, enquanto o programa a distância foi totalmente voluntário. Os estudantes foram avaliados em dois momentos, pré- e pós-teste, em relação a quatro dimensões de recursos de carreira. A motivação da experiência no programa foi avaliada após a intervenção. Os resultados indicam que, apesar de algumas diferenças entre as duas modalidades, ambas as intervenções de carreira foram eficazes, com ganhos em três das quatro dimensões de recursos de carreira. A perceção de conexão foi mais elevada na versão blended do programa, enquanto os participantes no formato a distância reportaram níveis mais elevados de autonomia durante o programa. Apesar disso, as variáveis motivacionais não apresentaram um poder preditivo relevante em relação aos ganhos nos recursos de carreira obtidos pela participação no programa. Em termos de implicações para a prática, os resultados sugerem a possibilidade de integrar intervenções nos currículos dos cursos superiores como forma de aumentar a permanência e de atingir diferentes públicos, sublinhando-se a importância de utilizar múltiplas abordagens para alargar o seu alcance. This research is financiall supported by nationa funds through the Portuguese Foundatio for Science and Technology (FCT), within the scope of the project PTDC/CED-EDG/0122/2020 and the projects UIDB/01661/2020, UIDB/04372/2020, UIDP/04372/2020 and UIDP/01661/2020.